2015
DOI: 10.1007/s10616-015-9848-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of medium selection on adipose-derived stem cell expansion and differentiation: implications for application in regenerative medicine

Abstract: The use of adipose-derived stem cells is wide-spread in both basic biology and regenerative medicine, due to the abundance of adipose tissue and the multipotent differentiation potential of the cells. However, the methods used to isolate and culture cells vary greatly between different research groups. Identification of medium formulations which provide rapid cell expansion while maintaining cell phenotype would have clear advantages. We compared growth and differentiation potential along the adipogenic lineag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Then, the undifferentiated state of ADSCs in the cell sheet was confirmed by the positive expression of CD105 and CD44 surface markers, as well as intracellular vimentin. Some studies revealed that ADSCs could differentiate into adipogenic [ 50 ], osteogenic, and chondrogenic lineages [ 51 ] after adding ascorbic acid [ 52 ] and long-term culturing [ 53 , 54 ], which has the risk of unwanted tissue formation. Hence, the undifferentiated state of ADSCs in cell sheets was confirmed using oil red O, Alizarin red, and Alcian blue staining following 10 days of culture with ascorbic acid or induction medium.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the undifferentiated state of ADSCs in the cell sheet was confirmed by the positive expression of CD105 and CD44 surface markers, as well as intracellular vimentin. Some studies revealed that ADSCs could differentiate into adipogenic [ 50 ], osteogenic, and chondrogenic lineages [ 51 ] after adding ascorbic acid [ 52 ] and long-term culturing [ 53 , 54 ], which has the risk of unwanted tissue formation. Hence, the undifferentiated state of ADSCs in cell sheets was confirmed using oil red O, Alizarin red, and Alcian blue staining following 10 days of culture with ascorbic acid or induction medium.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests using 25 defined genes to classify stem cells among others cell population together with cell surface markers by screening method. In the expansion culture, ASCs can achieve the maximum proliferation in 10% Fetal Bovine Serum (FBS) medium or even a mixture of low FBS and separate growth factor medium [32]. ASCs showed similar morphology and differentiation characteristics to MSCs from bone marrow [33].…”
Section: Characteristics Of Ascsmentioning
confidence: 99%
“…By contrast, ADSCs is derived from adipose tissue and is an ideal cell source for tissue engineering. It has the potential of extensive self‐renewal and pluripotent differentiation, and has been proved to differentiate into various cell types, such as adipocytes, osteocytes, chondrocytes , and endothelial cells . In addition, ADSCs possess several advantages as compared with the bone marrow mesenchymal stem cells (BMSCs).…”
Section: Discussionmentioning
confidence: 99%